Genomic Sequencing and Characterization of Two Auricularia Species from the Qinling Region: Insights into Evolutionary Dynamics and Secondary Metabolite Potential - Jianzhao Qi; Shijie Kang; Ming Zhang; Shen Qi; Yulai Li; Khassanov Vadim; Shuangtian Du; Minglei Li (Journal of Fungi)
Auricularia mushrooms, common bulk edible fungi, have considerable culinary and medicinal value. The Qinling region, represented by Zhashui County, is the main production area of Auricularia mushrooms in China. In this study, two wild Auricularia strains, M12 and M13, selected from the Qinling region for their desirable horticultural traits after domestication, were sequenced and characterized. Sequencing assembly results based on Illumina NovaSeq and PacBio Sequel II HiFi showed that the M12 genome was 56.04 Mbp in size, with 2.58% heterozygosity and 14.13% repetitive sequences, and was anchored on 12 chromosomes using HI-C technology. In contrast, the M13 genome was 52.10 Mbp, showed 2.34% heterozygosity, 13.89% repetitive sequences, and was assembled into 12 scaffolds. Collinearity analysis revealed extensive homologous regions between the M12 and M13 genomes. Phylogenetic analysis suggested that the divergence between M12 and M13 occurred approximately 4.575 million years ago (MYAs), while their divergence from Auricularia subglabra TFB-10046 SS5 occurred approximately 33.537 MYAs. Analyses of CYP450, carbohydrate-active enzymes (CAZymes), and gene family expansion/contraction revealed distinct genomic features between the two strains. SSR and LTR insertion time analyses revealed the genome dynamics of the two strains during their evolution. Analysis of secondary metabolite-associated biosynthetic gene clusters (BGCs) provides powerful clues to understand the origin of bioactive compounds in the Auricularia mushroom. This work represents the first genome sequencing of the Auricularia species derived from the Qinling region. These results not only enriched our understanding of the Auricularia genome but also provided an important genomic resource and theoretical basis for the subsequent genetic breeding, functional gene mining, and development of medicinal components of Auricularia species.